Competitive Options for Bio‐Syngas in High‐Temperature Heat Demand Sectors: Projections until 2050. Issue 3 (18th October 2022) - Mutlu, Özge; Jordan, Matthias; Zeng, Thomas; Lenz, Volker
Abstract: Germany aims to accomplish climate neutrality by 2045. Thus, it is important to take actions, especially to decarbonize the industrial heat sector. In this study, competitive options for bio‐syngas as substitute for natural gas in the German industry sectors with high‐temperature heat demand were projected until 2050 by integrating selected gasification technologies into the existing BenOpt (BioENergyOPTimisation) model for energy system modeling. The results showed that the integration of heat production from selected technologies is still not competitive for large‐scale applications, but other existing biomass technologies have the potential to become competitive. Methanation can be a possible option to tailor bio‐syngas quality for specific high‐temperature industrial applications. Abstract : Germany, as the largest industrial producer in the EU, aims to accomplish climate neutrality by 2045. Thus, it is important to take ambitious actions, especially to decarbonize the industrial heat sector. This study projects the competitive options for bio‐syngas in the German energy‐intensive sectors with high‐temperature heat demand until 2050.